PENGARUH KOMITMEN ORGANISASIONAL, KEPUASAN KERJA, DAN KETIDAKAMANAN KERJA TERHADAP KEINGINAN BERPINDAH DENGAN LOCUS OF CONTROL SEBAGAI PEMODERASI PADA PERAWAT - Rezqi Ananda Basid (JURNAL TEKNOLOGIA, 2019)
The purpose of this research is to analyze the effect of organizational commitment, job satisfaction, job insecurity to nurses turnover intention with locus of control as moderating variable. The sample comprised 150 nurses across a wide range of departments of a X hospital in Samarinda, East Kalimantan by using purposive sampling method who have been working from minimum 6 months. Following data collection, linear regression and hierarchical linear regression analysis to conduct data analysis. As the result, there is a significant negative effect of organizational commitment on nurses turnover intention. Job satisfaction has significant negative effect on nurses turnover intention and a significant job insecurity has significant positive effect on nurses turnover intention. However, locus of control does not plays as moderating variable on the effect of organizational commitment, job satisfaction and job insecurity on turnover intention. The findings of this study provide practical contribution and recommendation for organization to enhancing organizational commitment, job satisfaction and managing job insecurity.